From Comprehension Struggles to Reflective Growth: An Exploratory Study of Vodcast Use in Self-Directed Listening among Beginner EFL Learners - Hanifa, Rizaldy; Yusra, Siti Rahimah; Muhamanda, Riki; Saputra, Dwi Bayu; Alamsyah, Devy Kurnia (UNIB Press, 2025)
This qualitative study investigated the experiences of beginner English as a Foreign Language (EFL) learners utilizing English vodcasts for self-directed listening and metacognitive reflection. During a six-week intervention, 25 university students in West Sumatera, Indonesia, interacted with authentic spoken English input, supported by structured reflection. Data from Vodcast Analysis Templates and Oral Recordings documented comprehension processes, strategic responses, metacognitive insights, and affective engagement. Thematic analysis revealed four interconnected themes: challenges in listening comprehension, strategic responses to difficulties, metacognitive reflection and awareness, and affective engagement and motivation. Students often encountered difficulties with fast speech, unfamiliar accents, idiomatic expressions, and complex content, and they addressed these challenges through repetition, note-taking, and the use of subtitles. The templates facilitated learners in articulating breakdowns, evaluating listening behaviors, and recognizing growth. Overreliance on subtitles and repetition occasionally promoted superficial processing; some learners focused on vocabulary without incorporating it into discourse comprehension; and inconsistent oral responses indicated variable spoken fluency. The findings indicate that vodcasts can enhance autonomy, strategy use, and reflective learning, while also identifying areas that need instructional improvement.